2005
DOI: 10.1111/j.1529-8817.2005.00075.x
|View full text |Cite
|
Sign up to set email alerts
|

THE RECLASSIFICATION OF PFIESTERIA SHUMWAYAE (DINOPHYCEAE): PSEUDOPFIESTERIA, GEN. NOV.1

Abstract: Pfiesteria shumwayae Glasgow et Burkholder is assigned to a new genus Pseudopfiesteria gen. nov. Plate tabulation differences between Pfiesteria and Pseudopfiesteria gen. nov. as well as a maximum likelihood phylogenetic analysis based on rDNA sequence data warrant creation of this new genus. The Kofoidian thecal plate formula for the new genus is Po, cp, X, 4 0 , 1a, 6 0 0 , 6c, PC, 5 þ s, 5 0 0 0 , 0p, 2 0 0 0 0 . In addition to having six precingular plates, P. shumwayae comb. nov. also has a distinctive di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 27 publications
5
67
0
Order By: Relevance
“…The data on the abundances of O. marina and HNFs (2 to 5 μm in size) used in this estimation were obtained from water samples collected from solar salterns near Shiwha, Korea (in 2006), while those for G. cf. guttula (plus G. dominans) and HNFs (2 to 5 μm in size) were obtained from the water samples taken in Masan Bay, Korea (in 2004 and2005). For this estimation, we assumed that the ingestion rates of O. marina and G. cf.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data on the abundances of O. marina and HNFs (2 to 5 μm in size) used in this estimation were obtained from water samples collected from solar salterns near Shiwha, Korea (in 2006), while those for G. cf. guttula (plus G. dominans) and HNFs (2 to 5 μm in size) were obtained from the water samples taken in Masan Bay, Korea (in 2004 and2005). For this estimation, we assumed that the ingestion rates of O. marina and G. cf.…”
Section: Methodsmentioning
confidence: 99%
“…They have also been found to participate in reciprocal predator-prey interactions with mixotrophic dinoflagellates (Jeong et al 1997). Recently several HTD species such as Pfiesteria piscicida, Pseudopfiesteria shumwayae, Stoeckeria algicida, and Luciella masanensis (previously Lucy) have been newly discovered (Steidinger et al 1996, Litaker et al 2005, Jeong et al 2005b, Mason et al 2007). These heterotrophic dinoflagellates are harmful to finfish and shellfish due to their feeding on the blood cells and flesh of fish.…”
Section: Introductionmentioning
confidence: 99%
“…However, recently, several new species in this family have been discovered (Jeong et al 2005b, Litaker et al 2005, Mason et al 2007). The present study suggests that species in this family may have a distinct ecological niches and may be differentiated from each other based on their prey species, differential growth and ingestion rates (Lin et al 2004, Jeong et al 2005a, 2007a as well as the differential mortality rate due to predation as shown in the present study.…”
Section: Growth and Ingestion Ratesmentioning
confidence: 99%
“…Since the small heterotrophic dinoflagellate Pfiesteria piscicida (order Peridiniales and family Pfiesteriaceae) was first discovered in the early 1990s (Steidinger et al 1996), several more dinoflagellate species in the family Pfiesteriaceae, such as Cryptoperidiniopsis brodyi, Luciella atlantis, L. masanensis, Pseudopfiesteria shumwayae, and Stoeckeria algicida, have been discovered (Jeong et al 2005b, Litaker et al 2005, Steidinger et al 2006, Mason et al 2007). Both scientists and the public have paid attention to these dinoflagellates because some of the species are harmful to fish , Glasgow et al 2001, shellfish (Springer et al 2002, Shumway et al 2006, and humans (Schmechel & Koltai 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Pfiesteria shumwayae Glasgow et Burkholder (Glasgow et al 2001a) (also Pseudopfiesteria shumwayae (Glasgow et Burkholder) Litaker Mason Shields et Tester) (Litaker et al 2005) and the closely related P. piscicida Steidinger et Burkholder (Steidinger et al 1996) have been detected in New Zealand sediment and seawater samples by species specific PCR-based DNA probes (targeted at ribosomal DNA). Pfiesteria shumwayae has been detected in water and sediment samples collected from Kaipara Harbour (Northland), Golden and Tasman Bays (Nelson), Havelock (Marlborough), Wairewa/Lake Forsyth, Te Waihora/Lake Ellesmere and Muriwai/Coopers Lagoon (Canterbury), and the New River Estuary (Southland); one strain isolated from Tasman Bay sediments was tested for ichthyotoxicity and proved positive .…”
Section: Introductionmentioning
confidence: 99%